Means of interorganisational co-ordination of production: The role of transport and telecommunication - Antje Burmeister (European Regional Science Association (ERSA), 1998)
The purpose of this paper is to analyse the respective role of travel and telecommunication in interactions between the economic actors involved in particular production systems. Transportation and telecommunication systems are crucial to the efficient co-ordination and organisation of production systems, and the recent technological and organisational developments in both areas (new technologies of information and communication NTIC, high speed rail etc.) have important impacts on the way that firms organise the circulation of information and people. Most analyses of their respective roles refer to the antagonist theses of substitution versus complementarity of travelling and telecommunications. Schematically speaking, two very different forms of "immaterial" (i.e. not concerning goods transport) interactions in production systems can be opposed: exchange of codified, standardised information, which is possible over long distances through telecommunication devices, and co-ordination necessitating specific knowledge and collective learning processes. We will base our theoretical discussion on the well-known distinction between information and knowledge, derived from the theory of information. According to this definition, information, as long as it is codified and explicit, can travel through various channels, independently from people. Knowledge, in the sense of tacit, non codified information, is embedded in people and cannot travel in space independently. This distinction thus determines the choice between travelling (in order to establish face-to-face interactions) and telecommunication. The distinction is also important for understanding the need for proximity (permanent or temporary) in networks of producers: interactions involving a high content in idiosyncratic of tacit knowledge usually imply proximity between the participants. We will compare empirical data on the utilisation of travel and telecommunication in intra- and inter-firm co-ordination from several industrial and service sectors, collected in a qualitative survey of production plants in the North of France. These data allow us to analyse the characteristics of interactions between plants and headquarters and between firms and their suppliers, subcontractors and customers (frequency, duration, nature of information etc.) as well as the means chosen to support these interactions (e.g. meetings, EDI, telephone etc.). The comparison of behaviour in various industries gives interesting insights in sectoral patterns of interactions. It also shows that the determinants of choice go beyond the nature of information and include also history and social aspects such as conventions (sectoral or local).
Keywords: 330